PENGARUH PERUBAHAN FUNGSI RUANG TERBUKA PUBLIK DI KOTA LAMA SEMARANG TERHADAP CITRA KAWASAN - Fadzilla Rizka; Titien Woro Murtini; Atik Suprapti (TEKNIK, 2013)
Old City in Semarang as cultural reservation by Semarang undergone several changes over the times. One of that is change the function of public open space, every space change in an area affects on the image of the Old City in Semarang as the historical area. In the end, the change of public open space function affects on the image of The area of Old City in Semarang as Historical Area which existence is reserved. The purpose of this research is to acknowledge effects caused by the change of public open space function according to era development on the image of The area of Old City in Semarang as historical area fulfilled with buildings which have colonial architecture style. However, there are two kinds of variables in this research which are based on discussed research substance, they are independent variable which includes public open space function (ecology function, architectural/esthetical function, social function) and dependent variable which includes area image ( area identity, area structure, meaning of area). Both variables are analyzed using rationalistic quantitative method which techniques are multiple analysis technique and descriptive analysis. After doing analysis process, the results are: Taman Srigunting and Polder Tawang are successful to conduct each function, but generally, respondents say that Taman Srigunting is much better in doing its function as public open space than Polder Tawang. As for BTPN buiding, public agrees that the building disturbs the image of The area of Old City in Semarang because the design of the building does not adjust the neighborhood and the buildings surrounding it, and also, the condition of the empty building which is not taken care of and used gives more negative effect on the image of The area of Old City in Semarang. Conclusion drawn from this research is the existence of Taman Srigunting and Polder Tawang which have three functions as public open space such as ecology, esthetical, and social function, and the existence of BTPN building affect on the image of The area of Old City in Semarang. Key words :  function, open spaces, image